Is acute reperfusion therapy safe in acute ischemic stroke patients who harbor unruptured intracranial aneurysm?. (17th September 2015) - Mowla, Ashkan; Singh, Karanbir; Mehla, Sandhya; Ahmed, Mohammad K.; Shirani, Peyman; Kamal, Haris; Krishna, Chandan; Sawyer, Robert N.; Ching, Marilou; Siddiqui, Adnan H.; Levy, Elad I.; Snyder, Kenneth V.; et al.
Abstract : Background: Intracranial aneurysms are currently considered as contraindication for intravenous thrombolysis in acute ischemic stroke, very likely due to a possible increase in the risk of bleeding from aneurysm rupture; however, there is limited data available on whether intravenous thrombolysis is safe for acute ischemic stroke patients with pre‐existing intracranial aneurysms. Aims and/or hypothesis: To find out the safety of intravenous thrombolysis in acute ischemic stroke patients who harbor unruptured intracranial aneurysms. Methods: We retrospectively reviewed the medical records and cerebrovascular images of all the patients treated with intravenous thrombolysis for acute ischemic stroke in our center from the beginning of 2006 till the end of April 2014. Those with unruptured intracranial aneurysm present on cerebrovascular images prior to acute reperfusion therapy were identified. Post‐thrombolysis brain imaging was reviewed to evaluate for any intraparenchymal or subarachnoid hemorrhage related or unrelated to the aneurysm. Results: A total of 637 patients received intravenous thrombolysis for acute ischemic stroke in our center during an 8·3‐year period. Thirty‐three (5·2%) were found to have at least one intracranial aneurysms. Twenty‐three (70%) of those received only intravenous thrombolysis, and 10 patients received combination of intravenous and intra‐arterial thrombolysis. The size of the largest aneurysm was 10 mm in maximum diameter (range: 2–10 mm). The mean size of aneurysms was 4·8 mm. No symptomatic intracranial hemorrhage occurred among the 23 patients receiving only intravenous thrombolysis. Out of those who received a combination of intravenous and intra‐arterial thrombolysis, one developed symptomatic intracranial hemorrhage in the location of acute infarct, distant to the aneurysm location. Conclusion: Our findings suggest that neither intravenous thrombolysis nor combination of intravenous and intra‐arterial thrombolysis increases the risk of aneurysmal hemorrhage in acute ischemic stroke patients who harbor unruptured intracranial aneurysms less than 10 mm in diameter. Their listing in exclusion criteria for intravenous thrombolysis should be reconsidered to assure appropriate use of acute reperfusion therapy in this group of patients.